(untitled) (Lundiana: International Journal of Biodiversity, 2002)
Previous nest records and unusually modified mandibles of females have led workers to suggest that large carpenter bees (genus Xylocopa) in the subgenus Stenoxylocopa obligatory nest in bamboo and related plants with hollow stems. This paper reports the use of non-hollow substrate for nesting by one species in that subgenus. Nests found in the fibrous branches of Vellozia spp. (Velloziaceae) are described from two different sites. These nests are compared with those constructed in the hollow stems of bamboo that have been previously described. The data presented here do not support the hypothesis that geographical distributions of Stenoxylocopa are largely defined by the availability of hollow culms.